Evaluation of a Clinically Relevant Drug–Drug Interaction Between Rosuvastatin and Clopidogrel and the Risk of Hepatotoxicity - Ning, Chen; Su, Shengdi; Li, Jiaming; Kong, Dexuan; Cai, Hui; Qin, Zhiying; Xing, Han; Chen, Xijing; He, Jiake (Frontiers in Pharmacology, 2021)
Purpose The combination therapy of rosuvastatin (RSV) and the platelet inhibitor clopidogrel (CP) are widely accepted in the management of cardiovascular diseases. The objective of the present study was to identify the mechanism of RSV-CP DDI and evaluate the risk of hepatotoxicity associated with the concomitant use of CP. Methods We first studied the effect of CP and its major circulating metabolite, carboxylic acid metabolite (CPC), on RSV transport by over-expressing cells and membrane vesicles. Second, we investigated whether a rat model could replicate this DDI and then be used to conduct mechanistic studies and assess the risk of hepatotoxicity. Then, cytotoxicity assay in hepatocytes, biochemical examination and histopathology were performed to measure the magnitude of liver injury in the presence and absence of DDI. Results CP inhibited OATP1B1-mediated transport of RSV with an IC50 of 27.39 μM. CP and CPC inhibited BCRP-mediated RSV transport with IC50 values of < 0.001 μM and 5.96 μM, respectively. CP cocktail (0.001 μM CP plus 2 μM CPC) significantly inhibited BCRP-mediated transport of RSV by 26.28 %. Multiple i.g. doses of CP significantly increased intravenous RSV plasma AUC0-infinity by 76.29 % and decreased intravenous RSV CL by 42.62 %. Similarly, multiple i.g. doses of CP significantly increased i.g. RSV plasma AUC0-infinity by 87.48 % and decreased i.g. RSV CL by 43.27 %. CP had no effect on cell viability, while RSV exhibited dose-dependent cytotoxicity after 96 h incubation. Co-incubation of 100 μM CP and RSV for 96 h significantly increased intracellular concentrations and cell-to-medium concentration ratios of RSV, and reduced hepatocyte viability. Histological evaluation of liver specimens showed patterns of drug-induced liver injury. Cholestasis was found in rats in the presence of DDI. Conclusions CP is not a clinically relevant inhibitor for OATP1B1 and OATP1B3. The primary mechanism of RSV-CP DDI can be attributed to the inhibition of intestinal BCRP by CP combined with the inhibition of hepatic BCRP by CPC. The latter is likely to be more clinically relevant and be a contributing factor for increased hepatotoxicity in the presence of DDI.